IMPACT OF EL NINO, IOD, AND MONSOON IN DETERMINING THE POSSIBILITY OF EXTREME RAINFALL OVER SEVERAL REGION AT WEST JAVA - Eddy Hermawan; Atje Setiawan Abdullah; Budi Nurani Ruchjana; I Gede Nyoman Mindra; Shailla Rustiana (International Conference on Coastal and Delta Areas, 2015)
This study is mainly concerned an application of SST Niño 3.4, IOD and Monsoon index in determining the upcoming of the extreme rainfall over the Indonesian Maritime Continent (IMC). As one of the most important region located along the belt equator, the meteorological surface parameter over the IMC suspected is effecting mostly by the Monsoon system. This is a unique country, since located between two great continent (Asia and Australia) and two great ocean (Indian and Pacific). It indicates that the Sea Surface Temperature (SST) should become one of the most important parameter. Although, this region is affected by the Monsoon system, but another event called as the Indian Ocean Dipole (IOD) and El Niño suspected has a great effects also in determining the rainfall anomalies, especially for the extreme conditions. By this reason, we investigated the IOD and El-Niño index signal, especially the SST Niño 3.4 index. By assuming the drought and wet extreme condition is mostly affected by both parameter, we analysed the IOD and SST Niño 3.4 index for period of 1976 to 2000. For study cases, we concentrated to analyse the monthly rainfall data over Java Island, especially when the strongest El Niño and Dipole Mode event comes simultaneously. By applying the Multiple Linear Regression, we found the suitable formula of rainfall prediction over several region at West Java Province. Then, we applied the CPT (Climate Predictability Tools) technique, we found that drought extreme season is mostly affected by El-Niño event, while wet extreme season is mostly affected by the Dipole Mode event. Although, the recent value of SST Niño 3.4 gradually increase more than 2.4oC, however, if the IOD index still going on to the normal (neutral) condition, we suspect that until the end of this year, the drought extreme condition almost never attack to IMC, especially over Java Island. On the other hand, the Dipole Mode looks more responsible in determining the behaviour of rainfall anomalies over Java Island than El Niño event. In the end of ths study, we found that interaction between Monsoon, IOD and El-Niño will give more powerful to determine the rainfall anomalies for next year.